Community-Based Islamic Philanthropy Fundraising: Strategy, Challenges, and Opportunities at NU Care-LAZISNU Ponorogo - Vivi Nadia Fatmawati; Faruq Ahmad Futaqi (UIN Kiai Ageng Muhammad Besari Ponorogo, 2026)
Introduction: The collection of zakat, infaq, and alms (ZIS) funds through official institutions still faces various challenges, such as low public awareness, limited use of digital technology, and the non-optimal fundraising strategy carried out by zakat management institutions. On the other hand, there are still many people who distribute zakat directly to mustahik so that the potential for collecting zakat through institutions has not been maximized. Research Methods: This study uses a qualitative approach with a type of field research. Data collection was carried out through interviews, observations, and documentation with informants consisting of management, fundraising team, and related parties at NU Care Lazisnu Ponorogo Regency. Results: The results of the study show that the fundraising strategy of NU Care Lazisnu Ponorogo has applied a segmentation, targeting, positioning, branding, and tactical planning approach through the NU Coin program, dawn alms, social activities, social media, bank transfer services, and the use of the Nahdlatul Ulama organizational network. The implementation of the strategy is supported by the strong structural network of Nahdlatul Ulama, high public trust, and the existence of sustainable social programs. However, there are still obstacles in the form of limited human resources, suboptimal digitalization of fundraising, low public understanding of zakat through institutions, and operational constraints in the field. Conclusion: The fundraising strategy implemented has a positive impact on increasing public awareness in paying zakat through official institutions, although its implementation still requires strengthening aspects of digital technology, program innovation, and human resource development.